NANOSIZE STRUCTURE OF SELF-ASSEMBLY SODIUM DODECYL SULFATE: A STUDY BY SMALL ANGLE NEUTRON SCATTERING (SANS) - Edy Giri Rachman Putra; Abarrul Ikram (Indonesian Journal of Chemistry, 2006)
Small Angle Neutron Scattering (SANS) investigation on the self-assembly sodium dodecyl sulfate (SDS) molecules as a function of concentration and additives has been carried out. SANS spectrometer which has been completely installed at the neutron scattering laboratory (NSL) BATAN in Serpong, Indonesia has played most important role to determine the growth (size) and also the shapes of a micelle structure. In this works we report that spherical micelle structure with a radius of 16.7 Å will transform to ellipsoidal or rod-like micelle structure with the long axis extends up to 50 Å by increasing the concentration of SDS. Similar to that the micelle structures change by addition of salt in SDS micellar solutions. Keywords: nanostructure, micelle, self-assembly